1996
DOI: 10.1002/(sici)1098-2795(199608)44:4<525::aid-mrd12>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lectin binding to bovine sperm during heparin-induced capacitation

Abstract: Changes in the plasma membrane of bovine sperm during heparin‐induced capacitation were detected by the binding of fluorescent labeled lectins to unfixed sperm. Of the seven lectins evaluated, only binding of wheat germ agglutinin (WGA) changed with capacitation. Sperm were classified into one of 5 patterns (p1–p5) based on staining with WGA, presence or absence of propidium iodide (PI) staining (dead or alive), and acrosomal integrity (acrosome intact or reacted). The major changes associated with capacitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Rather, Ca 2+ may have increased the sensitivity of the functional assay used for detecting capacitation by enhancing the ability of cells to acrosome-react. Recently, an alteration in lectin-binding patterns has been associated with heparin-induced sperm capacitation and offers a promising method for evaluating capacitation independent of the acrosome reaction [43]. Regardless of actual mechanism, additional CaCl improved conditions for capacitating and inducing the acrosome reaction in oryx sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, Ca 2+ may have increased the sensitivity of the functional assay used for detecting capacitation by enhancing the ability of cells to acrosome-react. Recently, an alteration in lectin-binding patterns has been associated with heparin-induced sperm capacitation and offers a promising method for evaluating capacitation independent of the acrosome reaction [43]. Regardless of actual mechanism, additional CaCl improved conditions for capacitating and inducing the acrosome reaction in oryx sperm.…”
Section: Discussionmentioning
confidence: 99%
“…The BSPs interact with both cholesterol and phospholipids in the sperm plasma membrane. Following heparin binding, there is a loss of lectin binding to bovine sperm indicating the loss of sperm surface components [31,32]. The changes in surface components likely relate to a heparin induced loss of the BSPs over time that lead to a loss of membrane cholesterol and phospholipid [30].…”
Section: 0 Capacitation Of Spermmentioning
confidence: 99%
“…Capacitation of bovine sperm by heparin involves heparin binding to sperm, plasma membrane changes that can be detected by lectin binding, increases in sperm calcium uptake, increases in intracellular calcium (CaJ, and an increase in sperm CAMP (Parrish et al, 1988a(Parrish et al, ,b, 1993Medeiros and Parrish, 1991;Mahmoud and Parrish, 1992;Handrow et al, 1989;Uguz et al, 1994). In previous studies it was also reported that capacitation of bovine sperm was accompanied by an increase in pHi of 0.36 pH units that appears to be necessary for capacitation (Parrish et al, 1989b).…”
Section: Introductionmentioning
confidence: 99%